Violência x violência policial x capital social : estudo comparativo entre a cidade de Panambi e Itaqui-RS - Lucca, Humberto André Rodrigues (2014)
This dissertation is a comparative study between the levels of social and police violence between the cities of Panambi and Itaqui in the State of Rio Grande do Sul in comparison with the levels of the social capital. In the last five years from 2008 to 2012, Itaqui presented a bigger percentage within 37% if taken into account crimes like: murders, robberies with killed victims, steals and drug's traffic. Distinction that also shows itself present in face of police violence indicators. The research studied the reasons that lead a town to present higher rates of violence than another, following similar surveys (because some places have high crime’s rates and others not?) Bailing to both other sciences such as sociology and political science (social capital) through the application of a field survey, detecting smaller social capital in Itaqui town that also proved more violent and more police violence, also with greater inequality by GINI index than Panambi. Therefore the first chapter presents the social, economic, cultural and historical aspects. The second chapter discusses violence (social and police) based on database from SSP - RS, and based on existing records in correctional section of the Corporation. The third chapter discusses the social capital (theoretics), and its relation to violence, as well as the parameters for the survey formatting applied. Finally, the fourth chapter deals with the outcome of the research with comparative analysis between the studied municipalities where depth is the theoretical basis of the object of study. The research allowed to consider social factors, social capital and inequality correlates with different levels of social violence and police detected in each municipality. Those policies geared solely to an increase of more police, more police cars, more repression show to be ineffective in the long term to reduce violence.